The Effect of Providing Additional Food Based on Local Food on Weight Changes in Wasting Toddlers - Alvenda, Melvira; Makmur, Tri; Kurniasih, Ari; Siregar, Nondang Purnama (International Journal of Public Health Excellence (IJPHE), 2025)
Background: Wasting is a condition characterized by low body weight in relation to height or length. This condition is often caused by infections and inadequate nutritional intake in children. Objective: This study aims to determine the effect of Supplementary Feeding (SF) based on local food on the weight change of wasting toddlers. Methods: This study is a quasi-experimental research design using a pre-test and post-test framework over a period of 14 days. The sample consisted of 13 toddlers with wasting nutritional status who met the inclusion and exclusion criteria. Data analysis was performed using dependent t-test. Results: The findings showed that most respondents were male (76.9%) and aged between 1-3 years. The average weight before the provision of local food-based SF was 9.2 kg, and after the provision, it increased to 9.4 kg. The weight change difference before and after the SF was 0.2 kg, with the dependent t-test showing a p-value of 0.000. Conclusion: There is a significant effect of Supplementary Feeding based on local food on the weight change of toddlers with wasting status at Puskesmas Pangkalan Baru, Central Bangka Regency, Bangka Belitung Islands Province.